“MELAWAN KOTAK KOSONG”: ANALISIS MARKETING POLITIK ENAM PASANGAN CALON TUNGGAL PADA PILKADA 2020 DI JAWA TENGAH - Andreas Ryan Sanjaya; Yohanes Thianika Budiarsa (Interaksi: Jurnal Ilmu Komunikasi, 2024)
This study aims to understand the political marketing strategies implemented by campaign teams of single candidates in the contest of 2020 local election. Based on the literature review, there are only a few studies investigating the political marketing of single candidates in Indonesia’s local election. Given that, this study attempted to understand how the campaign teams of six electoral regencies in Central Java undertook their strategies to defeat the empty box. Data were collected by documenting the campaign materials uploaded on social media accounts that are officially registered to the General Election Commission (KPU). In addition, a series of interviews were administered to get data from several campaign team leaders. Afterward, the data analysis was done using the qualitative method. This study found that (1) the message formation process is very dependent on the characteristics of the prospective voters; 2) the campaign leader manages the cyber team to run campaigns through social media more effectively; 3) the campaign team integrates online and offline campaigns to build relationships with potential voters; and 4) the campaign team carries out a special strategy to deal with the power of the empty box movement.